Operationalizing ecosystem services for the mitigation of soil threats: A proposed framework. (August 2016) - Schwilch, Gudrun; Bernet, Lea; Fleskens, Luuk; Giannakis, Elias; Leventon, Julia; Marañón, Teodoro; Mills, Jane; Short, Chris; Stolte, Jannes; van Delden, Hedwig; Verzandvoort, Simone
Highlights: Integrating ecosystem services into land management decision-making is a challenge. An adapted framework for soil-related ecosystem services is needed; we present one. It helps identify changes caused by soil management and policies impacting on soil. It will be used to single out the most beneficial land management measures. Consistent terminology and clarity enable practical application with stakeholders. Abstract: Despite numerous research efforts over the last decades, integrating the concept of ecosystem services into land management decision-making continues to pose considerable challenges. Researchers have developed many different frameworks to operationalize the concept, but these are often specific to a certain issue and each has their own definitions and understandings of particular terms. Based on a comprehensive review of the current scientific debate, the EU FP7 project RECARE proposes an adapted framework for soil-related ecosystem services that is suited for practical application in the prevention and remediation of soil degradation across Europe. We have adapted existing frameworks by integrating components from soil science while attempting to introduce a consistent terminology that is understandable to a variety of stakeholders. RECARE aims to assess how soil threats and prevention and remediation measures affect ecosystem services. Changes in the natural capital's properties influence soil processes, which support the provision of ecosystem services. The benefits produced by these ecosystem services are explicitly or implicitly valued by individuals and society. This can influence decision- and policymaking at different scales, potentially leading to a societal response, such as improved land management. The proposed ecosystem services framework will be applied by the RECARE project in a transdisciplinary process. It will assist in singling out the most beneficial land management measures and in identifying trade-offs and win–win situations resulting from and impacted by European policies. The framework thus reflects the specific contributions soils make to ecosystem services and helps reveal changes in ecosystem services caused by soil management and policies impacting on soil. At the same time, the framework is simple and robust enough for practical application in assessing soil threats and their management with stakeholders at various levels.